Challenges of crafting junior high school students’ argumenta-tion skills: An exploration in an integrated STEM-EDP unit - Andina Armelia; Abdul Hakim; Muliati Syam; Atin Nuryadin; Nurul Fitriyah Sulaeman (Research and Development in Education (RaDEn), 2025)
Argumentation skills are crucial for students to analyze and evaluate complex information. This study was conducted to determine the argumentation pattern and quality of students' argumentation through STEM-EDP learning, namely, designing a simple projector challenge. This research was conducted at the Public Junior High School in Samarinda City. The sample in this study consisted of 34 students from grade VIII-4. Data in this study were collected using STEM-EDP-based worksheets that facilitate each stage of EDP, allowing for the collection of data in the form of students' argumentation on the topic of Light and Optical Devices. In the worksheet, students were directed to create a solution to the problem in the given letter, where the solution involves a simple projector. The results of this study indicate that the design of simple projects in STEM-EDP learning could facilitate students to argue, however, based on Toulmin's Argument Pattern (TAP) it was known that the argumentation patterns of students formed only 4 argumentation patterns out of 5 argumentation patterns that should be and the quality of argumentation dominates in low quality, namely at level 1 and level 2. Therefore, a further learning process that involves crafting more complex argumentation is needed.